Improving Students’ Retention in Mathematics Using Excel Spreadsheet Software Package in Port Harcourt, Nigeria - Onyekachi Uchechukwu Ahumaraeze; Chinyere Elizabeth Nlewedim (Pendidikan Matematika STKIP Kusuma Negara, 2024)
This study investigated the use of Excel spreadsheet software to improve students' retention in Mathematics in Port Harcourt. It aimed to compare the retention of students taught measures of central tendency using Excel with those taught using the deductive method and to determine if retention differed between male and female students taught with Excel. A quasi-experimental research design was employed. A sample of 133 students was selected from a population of 4,584 public junior secondary school students in Port Harcourt Local Government Area, Rivers State, using purposive sampling. Data were collected using a validated Measures of Central Tendency Retention Test. The experimental group used the Excel spreadsheet software package, while the control group used the deductive method. Analysis was conducted using mean, standard deviation, and analysis of covariance at a 0.05 significance level. The findings of the study revealed that the Excel spreadsheet package significantly enhances students' retention. Additionally, male students taught with the Excel spreadsheet package demonstrated higher retention than their female counterparts, though the difference was not statistically significant. It was recommended, among other suggestions, that Excel spreadsheets be used to teach measures of central tendency to improve students' retention.